POLYCULTURAL EDUCATION AS THE BASIS FOR THE FORMATION OF TOLERANCE IN THE PROCESS OF TEACHING - Gasimova, K.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
Modern society in the era of globalization is characterized by the emergence and dissemination of the ideas of multiculturalism. In this paradigm, cultural diversity is interpreted as an important component of socio-economic development in multi-ethnic states. Multicultural education is a direction in the development of education that has emerged as an alternative to monoculture. Multicultural education presents the presentation of such trends as the importance and formation of diversity in cultural interactions, the development of the individual's value potential with the obligatory recognition of his cultural identity. All this should be taken into account in the social policy of each state. The modern theory of multiculturalism, as a new educational paradigm, has also passed a significant path of formation and historical development, as a specific cultural process. Today, the education process is being formed taking into account cultural identity and integration interactions, the impact of globalization, socio-economic and socio-political sustainability. One of the main resources for the development of society and education in the 21st century is the accessibility and effectiveness of education focused on the formation of tolerance. The realities of globalization that are rapidly developing in the modern world space determine research in the field of multicultural education as the leading areas of pedagogical science. The formation of interest in multicultural education is caused by the need to develop intercultural communication, cooperation and cooperation, the emergence of the movement of ethnic and racial minorities for their identity in multi-ethnic regions and states.